Clinical profile and conversion rate to full psychosis in a prospective cohort study of youth affected by autism spectrum disorder and attenuated psychosis syndrome: A preliminary report - Riccioni, Assia; Siracusano, Martina; Vasta, Michelangelo; Ribolsi, Michele; Nastro, Federico Fiori; Gialloreti, Leonardo Emberti; Di Lorenzo, Giorgio; Mazzone, Luigi (Frontiers in Psychiatry, 2022)
Psychosis can occur at high rates in individuals with autism spectrum disorder (ASD). However, the detection of prodromal psychotic symptoms, including attenuated psychosis syndrome (APS), conditions at high risk of converting to full psychosis, has not been extensively investigated in ASD. We longitudinally evaluate a sample of young ASD individuals (age, mean±SD: 13±2.9) with (n=13) or without (n=18) concomitant APS through a standardized assessment of autistic (Autism Diagnostic Observation Schedule–Second Edition; ADOS–2) and psychotic (Structured Interview for Psychosis-Risk Syndromes, SIPS) symptoms and cognitive and adaptive skills. Individuals with other neuropsychiatric disorders were excluded. We estimated the conversion rate to full psychosis (according to SIPS criteria) over time (39.6±11.5 months) and explored the role of clinical variables at baseline in the transition to full psychosis. A conversion rate to full psychosis of 30.7% was found in ASD/APS. Conversion to full psychosis was not affected by the severity of the autistic and psychotic symptoms. At baseline, young individuals with ASD/APS who later converted to full psychosis showed lower cognitive performance (d=2.05) and greater impairment of adaptive social functioning profile (d=1.2) than those with ASD. The results of this preliminary report revealed that nearly a third of young individuals with ASD/APS convert to full psychosis over time. Conversion to full psychosis is affected by decreased cognitive and adaptive skills. Further investigations are needed to confirm the utility of APS detection and to better characterize the psychotic developmental trajectory in ASD, with consequent important implications on prognosis and therapeutic strategies.